PENGARUH ISU GLOBAL LINGKUNGAN TERHADAP KARYA DESAIN INTERIOR - Sri Wahyuni Trisna (Jurnal PATRA, 2019)
The decrease in environmental quality has a major influence on the quality of life. Improvement efforts to minimize negative impacts on humans and the environment need to be done, one of them is through interior design. This article will describe how interior designers can adapt and contribute to the environment in response to global issues that occur. Environmental-oriented interior design (eco-interior) is one solution for improving the environment and its inhabitants. The effort starts from the planning process, the selection of environmentally friendly materials, the proper implementation, maintenance, and the thought of production and post-production waste. By doing these efforts the designers are expected to be able to make a positive contribution to the environment that will add value in a design.